PENGARUH MEDIA SOSIAL TERHADAP PERUBAHAN NILAI BUDAYA SIPAKATAU, SIPAKALEBBI, DAN SIPAKAINGE’ DALAM KEHIDUPAN MASYARAKAT PERKOTAAN BULUKUMBA DI ERA DIGITAL - Khatima, Husnul; Firman Syah; Junaldi, Junaldi (Nusantara Hasana Journal, 2025)
This study aims to determine the influence of social media on changes in local cultural values of Sipakatau, Sipakalebbi, and Sipakainge' in the lives of Bulukumba urban communities in the digital era. This research uses a quantitative approach with data collection techniques through distributing a five-point Likert scale questionnaire to 25 respondents who live in urban areas and actively use social media. The data were analyzed descriptively quantitatively based on the score and percentage of each indicator. The results showed that the use of social media is high, with most respondents using it daily. Despite this, local cultural values are still relatively strongly maintained. The Sipakatau value scored 88%, indicating that respondents still respect differences of opinion and maintain communication ethics on social media. The value of Sipakalebbi scored the highest (average 95.2%), indicating strong respect for elders in the digital context. The value of Sipakainge' is also high with an average of 80.2%, which means that social media is still used as a means of reminding each other in kindness. However, the aspect of changing cultural values shows a tendency to shift, with scores of 73.6% and 78.4% on indicators related to the fading of manners. Thus, it can be concluded that social media has a significant influence on the preservation as well as the shift of local cultural values of the Perk community.